Y los clandestinos, ¿dónde están? Rastros da Ditadura Chilena, de 1973 a 1990 - Coradini, Rafaella de Aguiar (2017)
The text of the dissertation includes the effort to dialogue with the historiography about the History of the Chilean Dictatorship, also with historical theorists who deal with the paths of memory, relating it with reports made by survivors and characters of the dictatorships in the Southern Cone and in the case Of this dissertation, the Chilean Civil-Military Dictatorship (set./1973 to march/1990). And it ends with the audio-visual and biographical production already existing of the testimonies of several organizations, to explain how the clandestine happened in the country. The analysis was based on the questioning of the writing of the report, asking what and for whom it is addressed, as well as on the role of memory and its collaboration in clarifying the facts that occurred in a period of strong repression. Some survivors of human rights violations narrated their experiences from their understandings and emotions. Within this approach, the role of the State is also analyzed as a fundamental part in this process of reflection on dictatorial processes. For it is through the use and abuse of power that repression and violence are unleashed, knowing that such acts have become publicly known, when democracy is restored, and even before it, by the collaboration of those who have survived and prepared to recall the moments of clandestinity. This dissertation ends the activities carried out in the Post-Graduate Program in History of the Federal University of Santa Maria. This research focused on the area "History, Power and Culture". The research line "Culture, Migrations and Labor" collaborated in the discussion about the transformations of a society, with radical changes in its daily life, due to the Armed Forces' takeover of power, when a group of people came to live, from the coup, into the clandestinity. The objective was to interpret the works of memory in a sense of recognition and construction of the multiple Chilean identities, from the moment they arise, at the beginning of the 21st century, analyzing its documentary character for historiography. Thus, an analysis of the performance of human rights was made, starting in the 1990s, and how they became fundamental to achieve the objectives of these memories, a theme that circulates in the justification of the work, guaranteeing the prevalence of human rights in Societies that experienced great ruptures.